Design, Synthesis and Antiplasmodial Activities of a Library of Fluorine-Based 3-Benzylmenadiones - Matthieu Roignant; Jimmy Richard; Maxime Donzel; Matthias Rottmann; Pascal Mäser; Elisabeth Davioud-Charvet (Molecules)
Plasmodione is a potent early antiplasmodial compound. A metabolic study on mice treated with plasmodione revealed that 6-hydroxy–plasmodione was the main metabolite eliminated in the urine of treated mice. To block the metabolic pathway in the host, the introduction of fluorine at C-6 of the 3-benzylmenadione core was applied and showed potent antiplasmodial activity similar to that of the plasmodione analogue in vitro. In this work, a library of 38 6-fluoro-3-benzylmenadione analogues (a series) was constructed by incorporating structurally diverse groups in place of the 4-(trifluoromethyl) substituent present in the antiplasmodial plasmodione, via three synthetic routes. All new compounds were tested against the P. falciparum NF54 strain and for cytotoxicity with the rat L6 line. With a fluorine atom at C-6, A-a-21 was revealed to be the only compound from the a series, superior to the 6-H- analogue from the b series, with an IC50 value of 70 nM versus 200 nM. Then, five other fluorine-based 3-benzylmenadiones, in which the fluorine was introduced in various positions of the 3-benzylmenadione core, were synthetized to assist our understanding of the impact of fluorine on antiplasmodial potencies in vitro; in particular, the aim here was to compare the effects of human serum and P. berghei species in these drug screens. This was also conducted in vivo with the P. berghei-infected mouse model. In the P. berghei species assay, PD and the 4′-fluoro-3′-trifluoromethyl-benzylmenadione A-b-9 exhibited a similar antiplasmodial behavior toward P. falciparum versus P. berghei. In the human serum versus Albumax assays, only the 6-fluoro–plasmodione showed a lower shift factor between Albumax assays and human serum conditions, suggesting a lower protein binding for the 6-F-PD compared to plasmodione or A-b-9. In vivo, 6-fluoro–plasmodione proved to be the most potent 3-benzylmenadione, reducing parasitemia by 50% after oral administration at 50 mg/kg.